The magic, the life, the others: how can the imaginative dimension in reflective practice be used with student teachers? A learning experience through a self-study. Issue 2 (4th March 2019) - Elídóttir, Jórunn
ABSTRACT: In this article the author reflects upon the place imagination has in education and argues that imagination for adults is an important part of the reflective practice. The article explores the importance of going beyond the traditional way of thinking to capture the essence of understanding teaching and learning practice. The goal of this self-study is to create a way of professional development as a teacher educator which the author could utilise with teacher students. To accomplish that, the author travels to the three (imaginary) lands of reflective practice, and applies this as a way of reflective learning. The author demonstrates how reflective practices can draw together a dialogue between the embodied experience and understandings based on imaginative meanings. The author argues that reflective practice could benefit from a perspective that focuses on imaginative thoughts and more creative discussion in all aspects of education. Furthermore, to enhance students' reflective learning one must first and foremost be able to grasp the imaginative element within oneself in order to improve students' learning through reflective practice.